PENINGKATAN EFEKTIFITAS KUALITAS KANDANG AYAM MENGGUNAKAN INTERNET OF THINGS - Trisaputra, M.Riko; Nurul Solihah, Adelia; Mia Rosmiati (TEKTRIKA, 2023)
Chicken is one of the poultry that is familiar among the public. There are several things that need to be considered when raising chickens. One of them is the condition of the cage. In addition to the conditions of the cage, the influence of temperature, humidity and ammonia gas levels also affect the growth of the chickens. This is quite difficult for breeders who must regularly go to the pen to ensure the temperature, humidity and ammonia gas levels remain at ideal numbers. So, a system was created that can help monitor and control the chicken coop by utilizing Internet of Things (IoT) technology to display information on temperature, humidity, and ammonia gas levels in the chicken coop. This system is named the cage guard application. This system uses a DHT 22 sensor which functions to detect changes in temperature and humidity in the cage environment. In addition, this system uses MQ-137 to detect changes in ammonia levels in the cage. The process of storing data using firebase. To facilitate monitoring, this system uses an android application as a monitoring medium for the cage guard system. The coop guard application is also equipped with a camera that functions to see the movements of the chickens in the coop. This is done to observe the behavior of chickens through the camera. The purpose of using the camera is to make sure the chickens are not in a sick condition, which can be seen from whether a chicken is tired when it is in the cage. Based on the test results, this system can send data on the condition of the cage in real time. If this system is compared with similar products that are already on the market, the cost required for using the sensor is lower, resulting in an efficiency of 80.87%. Key Words: Chicken, Breeder, Temperature, Humidity, Amonia, Jaga Kandang